Utilization of membrane systems in beer processing - Esmaeili, Saeideh; Peivasteh roudsar, Leila; Mortazavian, Amir; Khosravi-Darani, Kianoush; Sohrabvandi, Sara (Archives of Advances in Biosciences, 2015)
Beer is the most consumed beverage after tea, carbonates, milk and coffee in the world and it continues to be a popular drink. One of the important reason for its popularity is that beer is a drink with a pleasant flavor, an attractive color and also because of its clarity. So, Membrane separation technology has become widely used in the food processing industryto attain these characteristics.As advantages of membrane filtration are included maintainingdissolved macromolecules that give the beer its flavor and functional properties while causes removal of yeast cells and turbidity colloids and also, reducing the components that cause turbidity of the bottled beer.Because of the potential of cross-flow microfiltration as a separation method for brewery, it has been investigated in the many of recent studies. Clarification of rough beer (RB) and pasteurization of clarified beer (CB) are as an application of cross-flow microfiltration (CFMF) in brewery. An important limitation in the performance of membrane processes is the fouling mechanism and the general effect of these phenomena, known as concentration polarization have described briefly in this review article. Moreover, the influence of important parameters in the filtration process such as temperature, pressure,type of membrane, pore size and the use of stamped membrane have been discussed.